Relationship between the limits of fit determined from B.S. 1916 and the functional requirements for interference fits - Scarr, A. J. (College of Aeronautics, 1963)
Introduction When a designer wishes to choose a shaft and hole deviation and tolerances, as, for example, an interference fit, he may be led to assume, when reading B.S.1916, that a particular fit combination will give the same functional characteristics over the entire size range covered by the standard. It is the intention of this note to show that this assumption is not necessarily valid, and that the fit combination_ required to meet a particular functional requirement will vary with size, These comments are not intended as a criticsm of the standard as such but, rather, that a supplement to the standard is required, to give the designer guidance on the choice of fit for particular functional requirements.